IMPLEMENTATION OF THE PREPARATION OF MSME FINANCIAL STATEMENTS BASED ON THE FINANCIAL ACCOUNTING STANDARDS OF MICRO, SMALL AND MEDIUM ENTITIES (SAK EMKM) IN WEAVING MSME IN KUPANG CITY - Meyulinda Aviana Elim (P3M- Politeknik Negeri Kupang, 2022)
This study aims to determine and analyze the implementation of the preparation of financial statements on MSME based on the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). This study uses a qualitative method. Variable operational definition refers to SAK EMKM. Data analysis used descriptive qualitative analysis method. The results of the study show that: (1) weaving MSME in the city of Kupang have not presented financial reports based on SAK EMKM. (2) weaving MSME in Kupang City have not carried out accounting procedures according to accounting standards